Mesomeric Betaines and N-Heterocyclic Carbenes of Pyrazole and Indazole - Schmidt, Andreas; Guan, Zong (Synthesis, 2012)
The chemistry of the N-heterocyclic carbenes pyrazol-3-ylidene and indazol-3-ylidene, and of the remote N-heterocyclic carbene pyrazol-4-ylidene, is reviewed. Heterocumulene adducts of pyrazol- and indazol-3-ylidene are pseudo-cross-conjugated heterocyclic mesomeric betaines, from which the corresponding N-heterocyclic carbenes can be generated by thermal cleavage of the carbene–heterocumulene bond. Cross-conjugated heterocyclic mesomeric betaines such as pyrazolium-4-carboxylates are formal 1:1 adducts of the heterocumulene carbon dioxide with the remote N-heterocyclic carbene pyrazol-4-ylidene. These relationships give rise to an interesting interplay between the two compound classes, N-heterocyclic carbenes and heterocyclic mesomeric betaines.1 Introduction2 Classifications 2.1 Mesomeric Betaines of Pyrazole and Indazole2.2 N-Heterocyclic Carbenes and Relatives of Pyrazole and Indazole3 Conjugated Mesomeric Betaines of Pyrazole and Indazole4 Ylides of Pyrazole 5 Cross-Conjugated Mesomeric Betaines and Remote N-Heterocyclic Carbenes of Pyrazole (Pyrazol-4-ylidenes)6 Pseudo-Cross-Conjugated Mesomeric Betaines and N-Heterocyclic Carbenes of Pyrazole (Pyrazol-3-ylidenes)7 Pseudo-Cross-Conjugated Mesomeric Betaines and N-Heterocyclic Carbenes of Indazole (Indazol-3-ylidenes)8 Conclusions
Keywords: mesoion; pyrazol-4-ylidene; pyrazol-3-ylidene; indazol-3-ylidene; carbene complex; catalysis; cyclic bent allene; abnormal N-heterocyclic carbene; remote N-heterocyclic carbene